2013
DOI: 10.1111/disa.12003
|View full text |Cite
|
Sign up to set email alerts
|

Flooding, resettlement, and change in livelihoods: evidence from rural Mozambique

Abstract: Post-disaster development policies, such as resettlement, can have major impacts on communities. This paper examines how and why people's livelihoods change as a result of resettlement, and relocated people's views of such changes, in the context of natural disasters. It presents two historically-grounded, comparative case studies of post-flood resettlement in rural Mozambique. The studies demonstrate a movement away from rain-fed subsistence agriculture towards commercial agriculture and non-agricultural acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 42 publications
1
57
0
2
Order By: Relevance
“…In India, impact assessments on resettlement have found problems such as landlessness, homelessness, joblessness, increased morbidity, food insecurity, loss of access to common property, social disarticulation, and marginalisation (Agnihotri et al, 1998). On the other hand, several studies have reported positive impacts on migrants, which can occur through livelihood diversification from subsistence farming to commercial farming and non-farming activities, higher incomes, better living conditions, and improvements in transportation and facilities (Arnall et al, 2013;Tashi and Foggin, 2012).…”
Section: Poverty Alleviation Resettlementmentioning
confidence: 99%
“…In India, impact assessments on resettlement have found problems such as landlessness, homelessness, joblessness, increased morbidity, food insecurity, loss of access to common property, social disarticulation, and marginalisation (Agnihotri et al, 1998). On the other hand, several studies have reported positive impacts on migrants, which can occur through livelihood diversification from subsistence farming to commercial farming and non-farming activities, higher incomes, better living conditions, and improvements in transportation and facilities (Arnall et al, 2013;Tashi and Foggin, 2012).…”
Section: Poverty Alleviation Resettlementmentioning
confidence: 99%
“…Moreover, they are destined to foreign market, while beans and corn of the slopes were traded in neighbor municipalities (RS5). The tendency to move away from traditional agriculture towards intensified agriculture was also found by Galipeau;Ingman;Tilt (2013) in their study about resettled farmers of the Mekong Basin in China and by Arnall et al (2013)such as resettlement, can have major impacts on communities. This paper examines how and why people's livelihoods change as a result of resettlement, and relocated people's views of such changes, in the context of natural disasters.…”
Section: Resultsmentioning
confidence: 65%
“…According to interviewees, 70% of the farmers from these municipalities who opted for individual resettlement have returned to their original municipalities. Resettlement project evasion was also verified by Arnall et al (2013) and by Obour et al (2016). Unable to purchase new properties because of the land price rise, they ended by providing basic services in the urban centers of these mu-nicipalities, changing their livelihhods (A4).…”
Section: Resultsmentioning
confidence: 99%
“…24 More than 80 percent of Mozambique's population is dependent on agriculture and most agriculture takes place in the country's extensive low-lying floodplains where the best soils are located. 25,26 The regular flooding in these areas can rapidly overwhelm local coping capacities. 27 While flooding often damages poorer countries more often, flooding is not unique to these countries.…”
Section: Floodsmentioning
confidence: 99%
“…Severe, damaging floods recently hit Australia in 2010 and northeastern US in 2012. [22][23][24][25][26][27][28] In the US, the amount of precipitation falling in the heaviest one percent of rain events increased by 20 percent in the past century, while total precipitation increased by seven percent. Over the last century, there was a 50 percent increase in the frequency of days with precipitation over four inches in the US upper Midwest.…”
Section: Floodsmentioning
confidence: 99%